2008
DOI: 10.1111/j.1469-8986.2007.00640.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of memory‐comparison‐based change detection in visual distraction

Abstract: The involvement of memory-comparison-based change detection in visual distraction was elucidated. Not only luminance increments that engaged memory-comparison-based change detection and refractoriness-based rareness detection but also luminance decrements that engaged only memory-comparison-based change detection caused behavioral distraction, which was mirrored by a posterior negativity (240-260 ms, posterior N2) and a broad positivity (420-460 ms, P3a) that reflected attentional capture. Preceding these effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
36
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 81 publications
6
36
0
Order By: Relevance
“…This assumption leads to the hypothesis that the functional significance of visual MMN might be the calling of attention that is required for the extensive processing of detected prediction-incongruent events. This hypothesis is indirectly supported by observations that visual MMN is often followed by attention-related ERP components, such as N2b and/or P300 Schröger, 2001, 2006;Kimura et al, 2008aKimura et al, , 2008cKimura et al, , 2008dKimura et al, , 2010dLiu and Shi, 2008;Wei et al, 2002).…”
Section: Functional Significancementioning
confidence: 78%
See 2 more Smart Citations
“…This assumption leads to the hypothesis that the functional significance of visual MMN might be the calling of attention that is required for the extensive processing of detected prediction-incongruent events. This hypothesis is indirectly supported by observations that visual MMN is often followed by attention-related ERP components, such as N2b and/or P300 Schröger, 2001, 2006;Kimura et al, 2008aKimura et al, , 2008cKimura et al, , 2008dKimura et al, , 2010dLiu and Shi, 2008;Wei et al, 2002).…”
Section: Functional Significancementioning
confidence: 78%
“…The second half of this review discusses the nature of the unintentional temporal-context-based prediction in vision. Here, on the basis of several key findings provided from visual MMN and other prediction-related studies, the nature of the unintentional prediction is discussed in terms of (1) behavioral indicators, (2) cognitive properties, and Schröger, , 2004and Schröger, , 2006Boll and Berti, 2009;Grimm et al, 2009), direction of motion (Amenedo et al, 2007;Hosák et al, 2008;Kremlácek et al, 2006;Lorenzo-Lopéz et al, 2004;PazoAlvarez et al, 2004aPazoAlvarez et al, , 2004bUrban et al, 2008), orientation (Astikainen et al, 2004(Astikainen et al, , 2008Czigler and Pató, 2009;Czigler and Sulykos, 2010;Flynn et al, 2009;Kimura et al, , 2010aKimura et al, , 2010bSulykos and Czigler, 2011), spatial frequency (Heslenfeld, 2003;Kenemans et al, 2003Kenemans et al, , 2008Maekawa et al, 2005Maekawa et al, , 2009Sulykos and Czigler, 2011; for a corresponding magnetoencephalography (MEG) study, see Kogai et al, 2011), contrast/ luminance (Kimura et al, 2008c(Kimura et al, , 2008d(Kimura et al, , 2010c(Kimura et al, , 2010dStagg et al, 2004;Wei et al, 2002), color (Czigler et al, 2002(Czigler et al, , 2004Czigler and Sulykos, 2010;Grimm et al, 2009;…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Katayama and colleagues reported that unique visual stimulus distracter designs (e.g., red squares on either side of the target stimulus) that "capture attention" from the target/standard task produce robust P3a components (Sawaki and Katayama, 2006, 2007. The nature of the distracter disruption has led to the direct assessment of ERP components linked to early stimulus feature evaluation, which engages the selective attention garnered by both stimulus context and task difficulty (Kimura et al, 2008a(Kimura et al, , 2008b(Kimura et al, , 2008cSawaki and Katayama, 2008b). Task difficulty affects this process as perceptually similar target and standard stimuli elicit larger P3a components than distracters presented in easy discrimination tasks (Demiralp et al, 2001;Hagen et al, 2006).…”
Section: Stimulus Context and Attentional Focusmentioning
confidence: 97%
“…Additionally, one might argue that the visual MMN reflected a greater activation level (i.e., a lower refractoriness or adaptation level) of afferent neurons that specifically respond to infrequent stimuli compared to those that specifically respond to frequent stimuli (i.e., a larger amplitude of visual N1 in response to infrequent compared to frequent stimuli, e.g., Alho et al, 1992;Berti and Schröger, 2006;Kenemans et al, 2003;Kimura et al, 2009). In the present study, however, we assessed deviant-related effects in response to infrequent low-luminance stimuli inserted in frequent high-luminance stimuli (i.e., sudden energetic decrements) that have been confirmed to engage memorymismatch processes but not to engage the greater activation level of afferent neurons (see e.g., Kimura et al, 2008a;Stagg et al, 2004 for the visual modality; Kaukoranta et al, 1989;Näätänen et al, 1989 for the auditory modality). Furthermore, it might be argued that the negativity treated as visual MMN was, in fact, associated with selective attention effects such as selection negativity (SN, Harter and Previc, 1978).…”
Section: Top-down Effects On Sequential Regularity Representation Indmentioning
confidence: 98%